The Critique of the Contemporary Islamic Movement by Fouad Zakaria - Wisam Hasan Flayih Twayej, Asst. Prof. Dr. (lark, 2026)
Fouad Zakaria criticized the contemporary Islamic movement in general, and the Islamic revivalist current in particular, focusing on its theoretical issues. He centered his critique on the problem of differentiating between Islam as a divine religious text and Muslims as human beings who try to understand and interpret it. He argued that this distinction cannot be realistically maintained. As proof, he pointed out that the critique of Islamic thought within the contemporary movement is essentially a critique of religion itself. This is because it is not possible to separate religious perceptions from the religious text—whether those perceptions are individual or collective—since they are derived from real-world experience before being shaped by the religious text. Despite the movement being driven by ideological motives and somewhat detached from practical application, Zakaria hoped that there would be a return to critical thinking, revision, and re-evaluation of ideas and practices to overcome obstacles. He called for renewal that stems from reality and reason, but in a way that harmonizes with the religious text and reason, based on an interpretive (ijtihadi) perspective.